Impact of Loss Aversion and Overconfidence Biases on Investor Decision-Making: The Mediating Role of Risk Tolerance - Bist, Rajesh Singh (KVM Research Journal, 2025)
The purpose of this study is to investigate how risk tolerance functions as a mediator between overconfidence and loss aversion in the decision-making process of individual investors. A structured questionnaire with multiple-choice and Likert scale items was used to gather data using a quantitative methodology. Responses were obtained by convenience sampling, and multiple regression analysis was performed on the data. Using Andrew F. Hayes’ Process V4.2 Macro, the mediating effect of risk tolerance was quantified. With a correlation coefficient of 0.623, the results show a moderately favorable association between investment decisions, loss aversion, and overconfidence. When risk tolerance is not present, overconfidence and loss aversion together explain 38.8% of the variance in investing choices. The study discovered that overconfidence and investment decision-making behavior are partially mediated by risk tolerance, with both direct and indirect effects being statistically significant. Similarly, the study discovered that while loss aversion’s direct impact on investment choices is statistically negligible, its indirect impact through risk tolerance is statistically substantial. While risk tolerance entirely mediates the association between loss aversion and investment decision-making behavior, it only partially mediates the relationship between overconfidence and investment decision-making behavior, according to the study. In order to promote logical decision-making, the study proposes including psychology and risk tolerance education into investor training programs, highlighting psychological biases and risk tolerance as mediators in investment behavior.